Good night, Gorilla - Rathmann, Peggy (New York, N.Y. : G.P. Putnam's Sons, 1994)
An unobservant zookeeper is followed home by all the animals he thinks he has left behind in the zoo.
Title from cover.
On board pages.
Keywords: Zoo animals -- Juvenile fiction; Zoos -- Juvenile fiction